Heavy metal concentracions in the soils and vegetation of the Béke-cave watershed (Aggtelek-karst, Hungary) - Kaszala, Rita; Bárány Kevei, Ilona (Acta Geographica Debrecina Landscape & Environment series, 2015)
Our research took place on karstic area in Aggtelek National Park in Hungary. The heavy metal content of soils with three different texture and in the plants of the natural vegetation (oak- , hornbeam-, corn leaves, greenery) were studied. Ratio of total (acid soluble) metal contents and bioavailable metal contents of the soils were calculated. Based on these results we determined the mobility of the metals in different soils. Used the metal contents of the soils and the vegetation we set up a sequence of the mobility of the metals between the soil and the most frequent plant species.